SAT0514 MIRAJE: A TRANSVERSAL THERAPEUTIC EDUCATION PROGRAM FOR CHILDREN AND ADOLESCENTS WITH CHRONIC INFLAMMATORY RHEUMATISM. (June 2019) - Rossi-Semerano, Linda; Dusser, Perrine; Lima, Margarete; Marie, Isabelle; Benleulmi, Fatima; Fahy, William; Koné-Paut, Isabelle; Hascoet, Chrystelle
Abstract : Background: Therapeutic patient education (TPE) is now recommended in the health care pathway of patients with chronic inflammatory rheumatism (CIR) but few pediatric programs are currently available. MIRAJE is a program for children and adolescents with CIR. It has been developed within a French health network (RESRIP (Réseau Rhumatismes Inflammatoires Pédiatriques)) to improve patient care for paediatric patients with CIR living in the Ile de France region. The originality of the program was to design cross-cutting TPE using common issues to different pathologies: the experience of chronic illness, the management of daily life, inflammatory attacks, long-term treatments, physical activity. Objectives: Assessment of acquisition of coping, self-care and safety skills. Methods: After signing a written consent, an educational assessment is conducted in an individual interview with the patients and/or parents (for children under 6 years old), by a member of the multidisciplinary team. Five group sessions and one self-injection session are offered to patients. During the collective sessions, patients and parents are reappointed according to 4 groups: the group of parents, that of adolescents (12-18 years), that of children (6-11 years) and that of toddlers (<6 years). To investigate the cognitive and behavioral impact of TPE on our patients and/or parents, we selected patients aged over 6 years who completed TPE program. A pre-post comparison was performed using a skill/knowledge questionnaire, based on three educational objectives: adaptation (8 skills), self-care (5 skills) and safety (1 skill), before and after the intervention. Results: We present the results of the first year of implementation of our TPE program (2017). Nineteen children and 20 parents attended at least one group session. Ten participants (6 children aged 6 to 17 and 4 parents) completed the TPE program. The diseases covered were juvenile idiopathic arthritis (7), systemic lupus (2) and mevalonate kinase deficiency (1). All participants improved their knowledge and skills following TPE with greatest improvement in management of inflammatory attacks (self-care) (10 patients after TPE versus 1 at initial assessment), chronic fatigue (6 versus 1) and in development of physical activity (8 versus 2) (adaptation). Otherwise, all 10 participants acquired self-care skills (4.1 versus 1.4 average skills per patient at initial assessment), 9 acquired coping skills (6.8 versus 2.6 skills) and 8 security skills. Regarding self-injection workshop, most patients (4/5) have acquired skills in subcutaneous self-injection. Conclusion: MIRAJE is the first French cross-cutting TPE program for children suffering from CIR and their parents. Although the number of participants having benefited from a full TPE program is relatively low, the first results are very encouraging. Indeed, TPE has allowed improving knowledge and skills for most children and parents. TPE allows a better acceptance of the disease and fosters patient's empowerment in daily management. We plan to expand our program to more patients with various RICs. Acknowledgement: All patients, their parents and health professionals who participated in the program Disclosure of Interests: Linda Rossi-Semerano Grant/research support from: Roche, Perrine Dusser: None declared, Margarete Lima: None declared, Isabelle Marie: None declared, Fatima Benleulmi: None declared, William Fahy: None declared, Isabelle Koné-Paut Grant/research support from: SOBI has supported drug product (anakinra) for the presented study, Consultant for: SOBI, Novartis, Pfizer, Abbvie, UCB, CHUGAI, ROCHE, Chrystelle Hascoet: None declared